Illegal Logging Eradication in the Perspective of National Criminal Law and Local Wisdom of Manggarai Community - Ngompat, Yohanes Leonardus; Finsensius Samara; Dwityas Witarti Rabawati (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This study discusses illegal logging as an environmental problem, especially in forestry. Illegal logging is a criminal offence, especially in violation of Law Number 41 of 1999 on Forestry and Law Number 18 of 2013 on Prevention and Eradication of Forest Destruction. Illegal logging is also prohibited based on the Manggarai community's local wisdom. The prohibition is motivated by the tradition of the Manggarai community, which utilizes the forest and recognizes the roko molas poco customary ritual. The ritual aims to inform the Manggarai people that anyone who wants to take a tree in the forest must bring a new tree seedling in exchange. This ritual also shows the responsibility to preserve the forest so it is not damaged. However, there are still people who commit illegal logging. This study aims to analyze and find regulations and concepts for eradicating illegal logging from the perspective of national criminal law and the local wisdom of the Manggarai community. The type of study used is empirical legal research. This study is a novelty because previous researchers should have specifically reviewed the role of local wisdom, especially the Manggarai community, in eradicating illegal logging. The results show that the role of criminal law and the local wisdom of the Manggarai community is significant in eradicating illegal logging crimes. Criminal law regulates the provision of criminal sanctions against individuals and groups who commit illegal logging. The same thing also applies to the local wisdom of the Manggarai community, namely the roko molas poco ritual that the taking or utilization of timber forest products must not conflict with the ritual; if it conflicts, then it will be subject to customary fines. Based on this explanation, not only national law has a role in combating illegal logging, but local wisdom law also has a role.